Scientification through privatization: POL-INTEL in Denmark - Karlsson, Björn; Galis, Vasilis (Theoretical criminology, 2025)
Based on the empirical case of the POL-INTEL platform used by the Danish police, which is a customized version of Palantir Technologies’ Gotham platform, this article traces the interrelation between scientification and policing in the digital era as articulated in and through a private actor. Ethnographic fieldwork, interviews, publicly available policy documents as well as documents detailing police practices, organization, ambitions and workflows are used to problematize digital policing platforms and practices in terms of wider criminological theories and models. We show that POL-INTEL epitomizes a historical trajectory of scientification through privatization by drawing together intelligence practices, market logics, and datafication methodologies. With this point of departure, we trace back how the entanglement of private actors and the police organization raises concerns about the black boxing of criminological procedures, and the delegation of decisions and knowledge within the criminal justice system to private actors lacking public values.